A kind of fine-count cashmere yarn and its production method
By adding biomass carbon nanotubes and ZnO QDs@SiO2 to the production of cashmere yarn and using protease treatment solution, the problems of medium and high cost, low efficiency and environmental protection in the production of traditional cashmere yarn are solved, and high-quality and high-end performance yarns are achieved. Line production.
Patent Information
- Application Number
- CN202411414215.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-11
AI Technical Summary
There are high costs, low yield efficiency, insufficient antistatic and antibacterial capabilities and environmental protection problems in the production process of traditional cashmere yarn, which is difficult to meet the needs of high-end applications.
Using the production method of worsted high-stranded cashmere yarn, cashmere yarn is formed by combining cashmere with biomass carbon nanotubes, ZnO QDs@SiO2 and protease treatment solution to form high-quality yarns, and biomass carbon nanotubes are used to enhance the anti-flushing and resistance of Electrostatic properties, ZnO QDs@SiO2 increases antibacterial properties and replaces chemical fiber treatment agents with protease treatment solution.
It significantly improves the structural integrity and environmental protection performance of the yarn, improves the anti-flushing, anti-static and antibacterial capabilities, is suitable for high-end market demand, and reduces the use of harmful chemicals.
Smart Images

Figure CN118932572B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cashmere processing, and in particular to a fine-count worsted cashmere yarn and a production method thereof. Background Art
[0002] Cashmere is widely used in the high-end textile market due to its excellent softness, lightness and warmth retention. Traditional cashmere yarn production mainly relies on mechanical spinning and ring spinning technologies. Although these technologies are relatively mature in industrial production, they still face many challenges when processing extremely fine fibers.
[0003] Currently, the high-count cashmere yarns on the market are mostly known for their soft feel and delicate texture. However, the production process of these yarns is often accompanied by high costs and low production efficiency. In addition, traditional spinning methods often have difficulty in ensuring anti-static and antibacterial capabilities while ensuring yarn strength, limiting the performance of the product in high-end applications. Another challenge is environmental protection. The spinning process usually requires a large amount of chemicals for fiber treatment and dyeing, which may burden the environment. Therefore, it is urgent to develop a production method that can both ensure yarn quality and meet environmental requirements. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a worsted high-count cashmere yarn and a production method thereof.
[0005] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is as follows: the present invention proposes a worsted high-count cashmere yarn, which comprises the following raw materials: 100 parts of cashmere, 6-8 parts of biomass carbon nanotubes, 20-35 parts of wool oil, 2-4 parts of ZnO QDs@SiO2, and 1-2 parts of protease treatment solution.
[0006] Preferably, the method for preparing biomass carbon nanotubes comprises the following steps:
[0007] ①, clean the potato peel waste with water, put it into an oven and dry it at 100℃ for 24 h, and then put it into a grinder to obtain biomass powder with a diameter of 300 μm;
[0008] ②, weigh 10 g of the biomass powder prepared in step ① and add it to 100 mL of distilled water, continue to add 10-12 mL of 85wt% phosphoric acid solution, mix well, centrifuge at 5000-6000 rpm to remove the supernatant 1, put the precipitate 1 in an oven at 100°C for 12 h, and place the dried precipitate 1 in a tube furnace and heat it to 450-500°C in a N2 atmosphere for pyrolysis for 30 min at a heating rate of 2°C / min. After naturally cooling to room temperature, wash it three times with distilled water and place the product 1 in an oven at 100°C for 12 h to obtain phosphoric acid-activated biomass;
[0009] ③, 4 g of the phosphoric acid-activated biomass prepared in step ② was added to 100 mL of distilled water, and 8-9 g of KOH was added. After mixing evenly, the supernatant 2 was removed by centrifugation at 5000-6000 rpm, and the precipitate 2 was placed in an oven at 100°C for 12 h, and then the dried precipitate 2 was placed in a tube furnace and heated to 450-500°C for pyrolysis for 30-40 min under a N2 atmosphere at a heating rate of 2°C / min. After naturally cooling to room temperature, the product 2 was washed three times with 1 mol / L HCl solution, and then the pH was neutralized with distilled water, and the product was placed in an oven at 100°C for 12 h to obtain a secondary activated biomass;
[0010] ④. Disperse 2 g of the secondary activated biomass prepared in step ③ in 50 mL of methanol, continue to add 10-12 g of melamine and 0.4-0.5 g of ferric oxalate, mix evenly under 150 W ultrasound for 30 min, continue stirring at 400 rpm for 4 h, filter and dry the filter cake in an oven at 80 ° C for 24 h, then place it in a tubular furnace for pyrolysis, heat it to 800-900 ° C at a rate of 4 ° C / min, maintain it for 40-60 min, cool it naturally to room temperature, wash the product 3 three times with distilled water, and then place it in an oven at 80 ° C for 24 h to obtain biomass carbon nanotubes.
[0011] Preferably, the crude oil comprises the following components in parts by weight: 30-40 parts of lauric acid ester, 30-40 parts of nonionic aqueous coconut oil, 6-10 parts of sorbitan monostearate, 4-7 parts of paraben, 4-6 parts of sodium carboxymethyl cellulose, 3-5 parts of polydimethylsiloxane, and 10-30 parts of water.
[0012] Preferably, the preparation method of ZnO QDs@SiO2 comprises the following steps:
[0013] I. Weigh 20-30 mmol of zinc acetate and dissolve it in 100 mL of ethanol, and stir at 450-500 rpm at room temperature to fully dissolve it to obtain a zinc ion solution;
[0014] II. Add 10 mL of 0.2 mol / L potassium hydroxide ethanol solution dropwise to the zinc ion solution prepared in step I, stir continuously at 500-600 rpm for 6-8 h, place in a centrifuge at 8000 rpm to remove the supernatant 3, wash the precipitate 3 twice with ethanol and water alternately, place in a vacuum drying oven at 60° C. and dry for 12 h to obtain zinc oxide quantum dots;
[0015] III. Place the zinc oxide quantum dots prepared in step II in 100 mL of distilled water, disperse them evenly under 200 W ultrasound for 10 min, add 50 μL of APTES, stir at 400 rpm for 1-2 h, add 2-4 mL of tetraethoxysilane, stir for 30 min, then add 200 μL of 25 wt% ammonia water, continue stirring for 4-6 h. After the reaction is completed, place it in a centrifuge at 8000 rpm to remove the supernatant 4, wash the precipitate 4 three times with ethanol and water alternately, place it in a vacuum drying oven at 60°C and dry it for 12 h to obtain ZnO QDs@SiO2.
[0016] Preferably, the protease treatment solution is a 1.5-2 wt % papain solution.
[0017] The present invention also provides a production method of fine-count worsted cashmere yarn, which specifically comprises the following steps:
[0018] S1. Mix cashmere and biomass carbon nanotubes evenly according to weight, add wool oil and ZnO QDs@SiO2, and place for 20-24 hours to obtain mixed fibers;
[0019] S2, placing the mixed fiber prepared in step S1 in a woolen carding machine for carding to form untwisted yarn;
[0020] S3, combining and drafting the untwisted yarns prepared in step S2 on a twisting roving frame, combing the untwisted yarns by drafting to form roving;
[0021] S4, drafting, twisting and winding the roving prepared in step S3 on a ring spinning frame to form spun yarn;
[0022] S5. The spun yarn prepared in step S4 is placed in 80° C. hot water for 20-30 min, then immersed in a protease treatment solution for 3-4 h, and then placed in boiling water to inactivate the enzyme for 20-30 min. After washing and drying, the fine worsted cashmere yarn is obtained.
[0023] The beneficial effects achieved by the present invention are as follows:
[0024] The fine-count worsted cashmere yarn and the production method thereof of the present invention have significant advantages in improving the quality of the yarn and environmental protection. The present invention effectively improves the structural integrity of the yarn by adding biomass carbon nanotubes and ZnO QDs@SiO2 as reinforcing agents. Biomass carbon nanotubes can significantly enhance the anti-pilling and antistatic capabilities of the yarn due to their special properties, while improving its far-infrared performance. ZnO QDs@SiO2 forms a tiny protective layer on the surface of the yarn, which not only increases the antibacterial properties of the yarn, but also makes the finished product more suitable for the needs of the high-end market. The use of biomass carbon nanotubes extracted from natural resources (such as potato peels, corn stalks, etc.) reduces environmental pollution in the production process. At the same time, the use of protease treatment liquid replaces the traditional chemical fiber treatment agent, reducing the use of harmful chemicals. The present invention not only improves product performance but also meets environmental protection requirements through a series of innovative material use and process optimization. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 is a transmission electron microscope image of ZnO QDs@SiO2 prepared in Example 1;
[0027] Figure 2 This is a scanning electron microscope image of the biomass carbon nanotubes prepared in Example 1. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0029] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0030] Example 1: This example proposes a worsted high-count cashmere yarn, which includes the following raw materials: 100 parts of cashmere, 6 parts of biomass carbon nanotubes, 30 parts of wool oil, 2 parts of ZnO QDs@SiO2, and 2 parts of protease treatment solution.
[0031] The method for preparing biomass carbon nanotubes comprises the following steps:
[0032] ①, clean the potato peel waste with water, put it into an oven and dry it at 100℃ for 24 h, and then put it into a grinder to obtain biomass powder with a diameter of 300 μm;
[0033] ②, weigh 10 g of the biomass powder prepared in step ① and add it to 100 mL of distilled water, then continue to add 12 mL of 85wt% phosphoric acid solution, mix well and centrifuge at 5000 rpm to remove the supernatant 1, put the precipitate 1 in an oven and dry it at 100°C for 12 h, and place the dried precipitate 1 in a tube furnace and heat it to 500°C for 30 min in a N2 atmosphere at a heating rate of 2°C / min. After naturally cooling to room temperature, wash it three times with distilled water and place the product 1 in an oven and dry it at 100°C for 12 h to obtain phosphoric acid-activated biomass;
[0034] ③, 4 g of the phosphoric acid-activated biomass prepared in step ② was added to 100 mL of distilled water, and 8 g of KOH was added. After mixing evenly, the supernatant 2 was removed by centrifugation at 5000 rpm, and the precipitate 2 was placed in an oven at 100°C for 12 h. Then, the dried precipitate 2 was placed in a tube furnace and heated to 500°C for pyrolysis for 30 min under a N2 atmosphere at a heating rate of 2°C / min. After naturally cooling to room temperature, the product 2 was washed three times with 1 mol / L HCl solution, and the pH was neutralized with distilled water. The product was placed in an oven and dried at 100°C for 12 h to obtain a secondary activated biomass;
[0035] ④. Disperse 2 g of the secondary activated biomass prepared in step ③ in 50 mL of methanol, continue to add 12 g of melamine and 0.5 g of ferric oxalate, mix evenly under 150 W ultrasound for 30 min, continue stirring at 400 rpm for 4 h, filter and dry the filter cake in an oven at 80 °C for 24 h, then place it in a tubular furnace for pyrolysis, heat it to 900 °C at a rate of 4 °C / min, hold it for 40 min, cool it naturally to room temperature, wash the product 3 three times with distilled water, and then place it in an oven at 80 °C for 24 h to obtain biomass carbon nanotubes.
[0036] The crude oil comprises the following components in parts by weight: 30 parts of lauric acid ester, 40 parts of nonionic aqueous coconut oil, 6 parts of sorbitan monostearate, 6 parts of p-hydroxybenzoate, 4 parts of sodium carboxymethylcellulose, 3 parts of polydimethylsiloxane and 30 parts of water.
[0037] The preparation method of the ZnO QDs@SiO2 comprises the following steps:
[0038] I. Weigh 20 mmol of zinc acetate and dissolve it in 100 mL of ethanol, and stir at 500 rpm at room temperature to fully dissolve it to obtain a zinc ion solution;
[0039] II. Add 10 mL of 0.2 mol / L potassium hydroxide ethanol solution dropwise to the zinc ion solution prepared in step I, stir continuously at 500 rpm for 6 h, place in a centrifuge at 8000 rpm to remove the supernatant 3, wash the precipitate 3 twice with ethanol and water alternately, place in a vacuum drying oven at 60° C. and dry for 12 h to obtain zinc oxide quantum dots;
[0040] III. Place the zinc oxide quantum dots prepared in step II in 100 mL of distilled water, disperse them evenly under 200 W ultrasound for 10 min, add 50 μL of APTES, stir at 400 rpm for 2 h, add 4 mL of tetraethoxysilane, stir for 30 min, then add 200 μL of 25 wt% ammonia water, continue stirring for 6 h. After the reaction is completed, place it in a centrifuge at 8000 rpm to remove the supernatant 4, wash the precipitate 4 three times with ethanol and water alternately, place it in a vacuum drying oven at 60°C and dry it for 12 h to obtain ZnO QDs@SiO2.
[0041] The protease treatment solution is a 2 wt % papain solution.
[0042] This embodiment also provides a method for producing fine worsted cashmere yarn, which specifically comprises the following steps:
[0043] S1. Mix cashmere and biomass carbon nanotubes evenly according to weight, add wool oil and ZnO QDs@SiO2, and place for 24 hours to obtain mixed fibers;
[0044] S2, placing the mixed fiber prepared in step S1 in a woolen carding machine for carding to form untwisted yarn;
[0045] S3, combining and drafting the untwisted yarns prepared in step S2 on a twisting roving frame, combing the untwisted yarns by drafting to form roving;
[0046] S4, drafting, twisting and winding the roving prepared in step S3 on a ring spinning frame to form spun yarn;
[0047] S5. The spun yarn prepared in step S4 is placed in 80° C. hot water for 20 min, then immersed in a protease treatment solution for 3 h, and then placed in boiling water for 20 min to inactivate the enzyme, and then washed and dried to obtain fine-count cashmere yarn.
[0048] Example 2: This example proposes a worsted high-count cashmere yarn, which includes the following raw materials: 100 parts of cashmere, 8 parts of biomass carbon nanotubes, 20 parts of wool oil, 4 parts of ZnO QDs@SiO2, and 1 part of protease treatment solution.
[0049] The method for preparing biomass carbon nanotubes comprises the following steps:
[0050] ①, clean the potato peel waste with water, put it into an oven and dry it at 100℃ for 24 h, and then put it into a grinder to obtain biomass powder with a diameter of 300 μm;
[0051] ②, weigh 10 g of the biomass powder prepared in step ① and add it to 100 mL of distilled water, then continue to add 10 mL of 85wt% phosphoric acid solution, mix well and centrifuge at 6000 rpm to remove the supernatant 1, put the precipitate 1 in an oven at 100°C for 12 h, and place the dried precipitate 1 in a tube furnace and heat to 450°C for 30 min in a N2 atmosphere at a heating rate of 2°C / min. After naturally cooling to room temperature, wash it three times with distilled water and place the product 1 in an oven at 100°C for 12 h to obtain phosphoric acid-activated biomass;
[0052] ③, 4 g of the phosphoric acid-activated biomass prepared in step ② was added to 100 mL of distilled water, and 9 g of KOH was added. After mixing evenly, the supernatant 2 was removed by centrifugation at 6000 rpm, and the precipitate 2 was placed in an oven at 100°C for 12 h. Then, the dried precipitate 2 was placed in a tube furnace and heated to 450°C for 40 min under a N2 atmosphere at a heating rate of 2°C / min. After naturally cooling to room temperature, the product 2 was washed three times with 1 mol / L HCl solution, and the pH was neutralized with distilled water. The product was placed in an oven and dried at 100°C for 12 h to obtain a secondary activated biomass;
[0053] ④. Disperse 2 g of the secondary activated biomass prepared in step ③ in 50 mL of methanol, continue to add 10 g of melamine and 0.45 g of ferric oxalate, mix evenly under 150 W ultrasound for 30 min, continue stirring at 400 rpm for 4 h, filter and dry the filter cake in an oven at 80 °C for 24 h, then place it in a tubular furnace for pyrolysis, heat it to 800 °C at a rate of 4 °C / min, hold it for 60 min, cool it naturally to room temperature, wash the product 3 three times with distilled water, and then place it in an oven at 80 °C for 24 h to obtain biomass carbon nanotubes.
[0054] The crude oil comprises the following components in parts by weight: 40 parts of lauric acid ester, 30 parts of nonionic aqueous coconut oil, 10 parts of sorbitan monostearate, 4 parts of p-hydroxybenzoate, 6 parts of sodium carboxymethylcellulose, 5 parts of polydimethylsiloxane and 10 parts of water.
[0055] The preparation method of the ZnO QDs@SiO2 comprises the following steps:
[0056] I. Weigh 30 mmol of zinc acetate and dissolve it in 100 mL of ethanol, and stir at 450 rpm at room temperature to fully dissolve it to obtain a zinc ion solution;
[0057] II. Add 10 mL of 0.2 mol / L potassium hydroxide ethanol solution dropwise to the zinc ion solution prepared in step I, stir continuously at 600 rpm for 8 h, place in a centrifuge at 8000 rpm to remove the supernatant 3, wash the precipitate 3 twice with ethanol and water alternately, place in a vacuum drying oven at 60° C. and dry for 12 h to obtain zinc oxide quantum dots;
[0058] III. Place the zinc oxide quantum dots prepared in step II in 100 mL of distilled water, disperse them evenly under 200 W ultrasound for 10 min, add 50 μL of APTES, stir at 400 rpm for 1 h, add 2 mL of tetraethoxysilane, stir for 30 min, then add 200 μL of 25 wt% ammonia water, continue stirring for 4 h. After the reaction is completed, place it in a centrifuge at 8000 rpm to remove the supernatant 4, wash the precipitate 4 three times with ethanol and water alternately, place it in a vacuum drying oven at 60°C and dry it for 12 h to obtain ZnO QDs@SiO2.
[0059] The protease treatment solution is a 1.5 wt% papain solution.
[0060] This embodiment also provides a method for producing fine worsted cashmere yarn, which specifically comprises the following steps:
[0061] S1. Mix cashmere and biomass carbon nanotubes evenly according to weight, add wool oil and ZnO QDs@SiO2, and place for 20 hours to obtain mixed fibers;
[0062] S2, placing the mixed fiber prepared in step S1 in a woolen carding machine for carding to form untwisted yarn;
[0063] S3, combining and drafting the untwisted yarns prepared in step S2 on a twisting roving frame, combing the untwisted yarns by drafting to form roving;
[0064] S4, drafting, twisting and winding the roving prepared in step S3 on a ring spinning frame to form spun yarn;
[0065] S5. The spun yarn prepared in step S4 is placed in 80° C. hot water for 30 min, then immersed in a protease treatment solution for 4 h, and then placed in boiling water for 25 min to inactivate the enzyme, and then washed and dried to obtain fine-count cashmere yarn.
[0066] Example 3: This example proposes a worsted high-count cashmere yarn, which includes the following raw materials: 100 parts of cashmere, 7 parts of biomass carbon nanotubes, 35 parts of wool oil, 3 parts of ZnO QDs@SiO2, and 1 part of protease treatment solution.
[0067] The method for preparing biomass carbon nanotubes comprises the following steps:
[0068] ①, clean the potato peel waste with water, put it into an oven and dry it at 100℃ for 24 h, and then put it into a grinder to obtain biomass powder with a diameter of 300 μm;
[0069] ②, weigh 10 g of the biomass powder prepared in step ① and add it to 100 mL of distilled water, then continue to add 11 mL of 85wt% phosphoric acid solution, mix well and centrifuge at 5500 rpm to remove the supernatant 1, put the precipitate 1 in an oven and dry it at 100°C for 12 h, and place the dried precipitate 1 in a tube furnace and heat it to 480°C in a N2 atmosphere for pyrolysis for 30 min at a heating rate of 2°C / min. After naturally cooling to room temperature, wash it three times with distilled water and place the product 1 in an oven and dry it at 100°C for 12 h to obtain phosphoric acid-activated biomass;
[0070] ③, 4 g of the phosphoric acid-activated biomass prepared in step ② was added to 100 mL of distilled water, and 8.5 g of KOH was added. After mixing evenly, the supernatant 2 was removed by centrifugation at 5500 rpm. The precipitate 2 was placed in an oven and dried at 100°C for 12 h. The dried precipitate 2 was then placed in a tube furnace and heated to 480°C for 35 min under a N2 atmosphere at a heating rate of 2°C / min. After naturally cooling to room temperature, the product 2 was washed three times with 1 mol / L HCl solution, and the pH was neutralized with distilled water. The product was placed in an oven and dried at 100°C for 12 h to obtain a secondary activated biomass;
[0071] ④. Disperse 2 g of the secondary activated biomass prepared in step ③ in 50 mL of methanol, continue to add 11 g of melamine and 0.4 g of ferric oxalate, mix evenly under 150 W ultrasound for 30 min, continue stirring at 400 rpm for 4 h, filter and dry the filter cake in an oven at 80 °C for 24 h, then place it in a tubular furnace for pyrolysis, heat it to 850 °C at a rate of 4 °C / min, hold it for 50 min, cool it naturally to room temperature, wash the product 3 three times with distilled water, and then place it in an oven at 80 °C for 24 h to obtain biomass carbon nanotubes.
[0072] The crude oil comprises the following components in parts by weight: 35 parts of lauric acid ester, 35 parts of nonionic aqueous coconut oil, 8 parts of sorbitan monostearate, 7 parts of p-hydroxybenzoate, 5 parts of sodium carboxymethylcellulose, 4 parts of polydimethylsiloxane and 20 parts of water.
[0073] The preparation method of the ZnO QDs@SiO2 comprises the following steps:
[0074] I. Weigh 25 mmol of zinc acetate and dissolve it in 100 mL of ethanol, and stir at 480 rpm at room temperature to fully dissolve it to obtain a zinc ion solution;
[0075] II. Add 10 mL of 0.2 mol / L potassium hydroxide ethanol solution dropwise to the zinc ion solution prepared in step I, stir continuously at 550 rpm for 7 h, place in a centrifuge at 8000 rpm to remove the supernatant 3, wash the precipitate 3 twice with ethanol and water alternately, place in a vacuum drying oven at 60° C. and dry for 12 h to obtain zinc oxide quantum dots;
[0076] III. Place the zinc oxide quantum dots prepared in step II in 100 mL of distilled water, disperse them evenly under 200 W ultrasound for 10 min, add 50 μL of APTES, stir at 400 rpm for 2 h, add 3 mL of tetraethoxysilane, stir for 30 min, then add 200 μL of 25 wt% ammonia water, continue stirring for 5 h. After the reaction is completed, place it in a centrifuge at 8000 rpm to remove the supernatant 4, wash the precipitate 4 three times with ethanol and water alternately, place it in a vacuum drying oven at 60°C and dry it for 12 h to obtain ZnO QDs@SiO2.
[0077] The protease treatment solution is a 1.8 wt % papain solution.
[0078] This embodiment also provides a method for producing fine worsted cashmere yarn, which specifically comprises the following steps:
[0079] S1. Mix cashmere and biomass carbon nanotubes evenly according to weight, add wool oil and ZnO QDs@SiO2, and place for 22 hours to obtain mixed fibers;
[0080] S2, placing the mixed fiber prepared in step S1 in a woolen carding machine for carding to form untwisted yarn;
[0081] S3, combining and drafting the untwisted yarns prepared in step S2 on a twisting roving frame, combing the untwisted yarns by drafting to form roving;
[0082] S4, drafting, twisting and winding the roving prepared in step S3 on a ring spinning frame to form spun yarn;
[0083] S5. The spun yarn prepared in step S4 is placed in 80° C. hot water for 25 min, then immersed in a protease treatment solution for 3 h, and then placed in boiling water for 30 min to inactivate the enzyme, and then washed and dried to obtain fine-count cashmere yarn.
[0084] Comparative Example 1: This comparative example proposes a fine-count worsted cashmere yarn, which differs from Example 1 only in that no biomass carbon nanotubes are added, and the remaining components, component contents, and experimental steps are the same as those of Example 1.
[0085] Comparative Example 2: This comparative example proposes a fine-count worsted cashmere yarn, which differs from Example 1 only in that ZnO QDs@SiO2 is not added, and the remaining components, component contents, and experimental steps are the same as those in Example 1.
[0086] Experimental Example 1: The microscopic morphology of ZnO QDs@SiO2 prepared in Example 1 was observed using a transmission electron microscope, and the microscopic morphology of the biomass carbon nanotubes prepared in Example 1 was observed using a scanning electron microscope.
[0087] Figure 1 This is a transmission electron microscope image of the ZnO QDs@SiO2 prepared in Example 1. As shown in the figure, multiple ZnO QDs are coated with SiO2. The diameter of the ZnO QDs is about 8 nm. Coating with SiO2 can improve the chemical stability of ZnO QDs and reduce the biological toxicity of ZnO QDs. Figure 2 3 is a scanning electron microscope image of the biomass carbon nanotubes prepared in Example 1. As shown in the figure, the synthesized biomass carbon nanotubes are relatively uniform, and the tube diameter is about 400 nm, indicating that the biomass carbon nanotubes are successfully synthesized.
[0088] Experimental Example 2: The fine-count worsted cashmere yarns prepared in Examples 1-3 and Comparative Examples 1-2 were made into fabrics for performance testing;
[0089] According to the standard GB / T 4802.1-2008 "Determination of pilling properties of textile fabrics Part 1: Circular locus method", the pilling grade of fabrics made of cashmere yarn was tested, among which, grade 1 is severe pilling and (or) pilling on the surface, and balls of different sizes and densities cover the entire surface of the sample, grade 2 is obvious pilling and (or) pilling on the surface, and balls of different sizes and densities cover most of the surface of the sample, grade 3 is moderate pilling and (or) moderate pilling on the surface, and balls of different sizes and densities cover part of the surface of the sample, grade 4 is slight pilling and (or) slight pilling on the surface, and grade 5 is no change;
[0090] According to the standard GB / T 30127-2013 "Testing and Evaluation of Far-Infrared Performance of Textiles", the far-infrared emissivity and far-infrared radiation temperature rise performance of fabrics made of cashmere yarn were tested;
[0091] The electrostatic properties of fabrics made of cashmere yarn were evaluated according to the standard GB / T 12703.1-2021 "Evaluation of electrostatic properties of textiles Part 1 Corona charging method", among which, excellent is half-life (HDT) ≤ 10 s, better is 10 s < half-life (HDT) ≤ 30 s, generally 30 s < half-life (HDT) ≤ 60 s, and poor is half-life (HDT) > 60 s;
[0092] According to the standard GB / T 20944.1-2007 “Evaluation of antibacterial properties of textiles Part 1: Agar plate diffusion method”, the antibacterial properties of fabrics made of cashmere yarn were evaluated according to Table 1, and the test results are shown in Table 2.
[0093] Table 1 Evaluation of antibacterial effect
[0094]
[0095] Table 2 Performance test data
[0096]
[0097] As shown in Table 2, the high-count cashmere yarn prepared in Examples 1-3 and Comparative Example 2 has good anti-pilling ability, and the high-count cashmere yarn prepared in Comparative Example 1 has moderate pilling, indicating that the added carbon nanotubes can effectively improve the anti-pilling ability of the high-count cashmere yarn. The high-count cashmere yarn prepared in Examples 1-3 and Comparative Example 2 has a higher far-infrared emissivity than that in Comparative Example 1, both of which are greater than 0.88; at the same time, the high-count cashmere yarn prepared in Examples 1-3 also has a higher far-infrared temperature rise than that in Comparative Example 1-2, indicating that biomass carbon nanotubes and ZnO QDs@SiO2 can improve the far-infrared performance of high-count cashmere yarn. The high-count cashmere yarn prepared in Examples 1-3 has excellent antistatic ability, which is due to the conductivity and high dispersibility of carbon nanotubes and ZnO QDs@SiO2, which does not affect other properties of the high-count cashmere yarn while improving its antistatic ability. The high-count cashmere yarns prepared in Examples 1-3 and Comparative Example 1 have good antibacterial properties, while the antibacterial properties of Comparative Example 2 are limited due to the lack of ZnO QDs@SiO2. The above performance tests show that the fine-count cashmere yarns proposed in the present invention have excellent properties and are suitable for the needs of the high-end market.
[0098] The present invention and its implementation methods are described above, and such description is not restrictive, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design methods and embodiments similar to the technical solution without creativity, which should all fall within the protection scope of the present invention.
Claims
1. A fine-count worsted cashmere yarn, characterized in that: The fine-count cashmere yarn comprises the following raw materials: 100 parts of cashmere, 6-8 parts of biomass carbon nanotubes, 20-35 parts of wool oil, 2-4 parts of ZnO QDs@SiO2, and 1-2 parts of protease treatment solution; The method for preparing biomass carbon nanotubes comprises the following steps: ①, clean the potato peel waste with water, dry it and then crush it to obtain biomass powder; ②, adding the biomass powder prepared in step ① into distilled water, continuing to add phosphoric acid solution, mixing evenly and centrifuging to remove the supernatant, drying the precipitate and placing it in a tube furnace for pyrolysis under a N2 atmosphere, cooling to room temperature, washing with distilled water and drying the product to obtain phosphoric acid-activated biomass; ③. Add the phosphoric acid activated biomass prepared in step ② into distilled water, continue to add KOH, mix well, centrifuge to remove the supernatant, dry the precipitate, place it in a tube furnace for pyrolysis under N2 atmosphere, cool to room temperature, wash the product with HCl solution, neutralize the pH with distilled water, and dry to obtain the secondary activated biomass; ④, dispersing the secondary activated biomass prepared in step ③ in methanol, continuing to add melamine and ferric oxalate, ultrasonically mixing evenly, continuing to stir, filtering and drying the filter cake, and then placing it in a tubular furnace for pyrolysis, cooling the product to room temperature, and drying to obtain biomass carbon nanotubes; The preparation method of the ZnO QDs@SiO2 comprises the following steps:
1. Weigh zinc acetate and dissolve it in ethanol to obtain a zinc ion solution; II. Add potassium hydroxide ethanol solution dropwise to the zinc ion solution prepared in step I, continue stirring for 6 to 8 hours, wash the obtained precipitate alternately with ethanol and water, and dry to obtain zinc oxide quantum dots; III. Disperse the zinc oxide quantum dots prepared in step II in distilled water evenly, add APTES and stir, continue to add tetraethoxysilane, stir evenly, add ammonia water and continue to stir, wash alternately with ethanol and water to obtain a precipitate, and dry to obtain ZnO QDs@SiO2.
2. The fine-count worsted cashmere yarn according to claim 1, characterized in that: The crude oil comprises the following components in parts by weight: 30-40 parts of lauric acid ester, 30-40 parts of nonionic aqueous coconut oil, 6-10 parts of sorbitan monostearate, 4-7 parts of p-hydroxybenzoic acid ester, 4-6 parts of sodium carboxymethyl cellulose, 3-5 parts of polydimethylsiloxane and 10-30 parts of water.
3. The fine-count worsted cashmere yarn according to claim 2, characterized in that: The protease treatment solution is a 1.5-2wt% papain solution.
4. A method for preparing the worsted high count cashmere yarn according to any one of claims 1 to 3, characterized in that: The specific steps include: S1. Mix cashmere and biomass carbon nanotubes evenly according to weight, add wool oil and ZnO QDs@SiO2, and place for 20-24 hours to obtain mixed fibers; S2, placing the mixed fiber prepared in step S1 in a woolen carding machine for carding to form untwisted yarn; S3, combining and drafting the untwisted yarns prepared in step S2 on a twisting roving frame, combing the untwisted yarns by drafting to form roving; S4, drawing, twisting and winding the roving prepared in step S3 on a ring spinning frame to form spun yarn; S5. The spun yarn prepared in step S4 is placed in hot water for 20-30 min, immersed in a protease treatment solution for 3-4 h, and then placed in boiling water to inactivate the enzyme for 20-30 min. After washing and drying, the fine worsted cashmere yarn is obtained.
Citation Information
Patent Citations
Yarn spinning technology for semi-worsted cashmere wool and cotton fiber colored spun yarn and yarn
CN104878491A
Cashmere fiber with natural and gentle luster and fatigue resistance and manufacturing method of cashmere fiber
CN105088454A
Flame-retardant antibacterial cashmere blend yarn
CN109023621A
Carbon nanotube elastic core-spun yarn as well as preparation method and application thereof
CN112391712A
Preparation process and application of antistatic cashmere blended yarn
CN118065023A